MG1141A as a Highly Potent Monoclonal Neutralizing Antibody Against SARS-CoV-2 Variants - Lee, Sua; Jang, Shina; Kang, Jihoon; Park, Soo Bin; Han, Young Woo; Nam, Hyemi; Kim, Munkyung; Lee, Jeewon; Cho, Ki Joon; Kim, Jeonghun; Oh, Miyoung; Ryu, Jihye; et al. (Frontiers in Immunology, 2021)
Since the coronavirus disease outbreak in 2019, several antibody therapeutics have been developed to treat severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections. Antibody therapeutics are effective in neutralizing the virus and reducing hospitalization in patients with mild and moderate infections. These therapeutics target the spike protein of SARS-CoV-2; however, emerging mutations in this protein reduce their efficiency. In this study, we developed a universal SARS-CoV-2 neutralizing antibody. We generated a humanized monoclonal antibody, MG1141A, against the receptor-binding domain of the spike protein through traditional mouse immunization. We confirmed that MG1141A could effectively neutralize live viruses, with an EC50 of 92 pM, and that it exhibited effective Fc-mediated functions. Additionally, it retained its neutralizing activity against the alpha (UK), beta (South Africa), and gamma (Brazil) variants of SARS-CoV-2. Taken together, our study contributes to the development of a novel antibody therapeutic approach, which can effectively combat emerging SARS-CoV-2 mutations.